Molecular and morphological analysis of Henneguya jundiai n. sp. (Cnidaria: Myxosporea), a new parasite of the gills of Rhamdia quelen in Brazil - Negrelli, Débora Caroline [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Tagliavini, Vinícius Panciera [UNESP]; Abdallah, Vanessa Doro; de Azevedo, Rodney Kozlowiski (My University, 2019)
Plasmodia containing spores of a new species of myxozoan, Henneguya jundiai n. sp., were found in the gill arches of Rhamdia quelen catfish. The present study describes H. jundiai n. sp. based on morphological and molecular analysis. The mature spores were elongated and measured 26.9 ± 1.9 (22.9–29.2) μm in total spore length, 9.5 ± 0.4 (8.8–10.0) μm in spore body length, 4.6 ± 0.4 (4.1–5.5) μm in spore body width, 17.3 ± 1.8 (14.1–19.8) μm in tail length, 4.9 ± 0.3 (4.6–5.5) μm in polar capsule length and 1.4 ± 0.2 (1.2–1.7) μm in polar capsule width. The polar filaments had 6–7 coils. Histological analysis revealed the formation of a large plasmodium connected to the gill arch through the epithelial tissue. Ultrastructural analysis revealed the presence of a binucleated sporoplasm, as well as the polar capsules and the coils of the polar filament. Phylogenetic analysis found that H. jundiai n. sp. is located within a subclade formed by species of Henneguya which parasitize siluriform fish from Brazil. Henneguya jundiai n. sp. appears as a sister species of H. quelen. The results of the analyzes clearly indicated the existence of a new species, H. jundiai.
Keywords: Heptapteridae; Histopathology; Myxobolidae; Phylogeny; Ultrastructure